"Cookbook medicine": Exploring the impact of opioid prescribing limits legislation on clinical practice and patient experiences - Elizabeth Joniak-Grant; Natalie A. Blackburn; Nabarun Dasgupta; Maryalice Nocera; Samantha Wooten Dorris; Paul R. Chelminski; Timothy S. Carey; Shabbar I. Ranapurwala (Elsevier, 2023)
Opioid dependence and overdose are serious public health concerns. States have responded by enacting legislation regulating opioid-prescribing practices. Through in-depth interviews with clinicians, state officials, and organizational stakeholders, this paper examines opioid prescribing limits legislation (PLL) in North Carolina and how it impacts clinical practice. Since the advent of PLL, clinicians report being more mindful when prescribing opioids and as expected, writing for shorter durations for both acute and postoperative pain. But clinicians also report prescribing opioids less frequently for acute pain, refusing to write second opioid prescriptions, foisting responsibility for patient pain care onto other clinicians, and no longer writing opioid prescriptions for chronic pain patients. They directly credit PLL for these changes, including institutional policies enacted in response to PLL, and, to a lesser degree, notions of "do no harm." However, we argue that misapplication of and ambiguities in PLL along with defensive medicine practices whereby clinicians and their institutions center their legal interests over patient care, amplify these restrictive changes in clinical practice. Clinicians' narratives reveal downstream consequences for patients including undertreated pain, being viewed as drug-seeking when questioning opioid-prescribing decisions, and having to overuse the medical system to achieve pain relief.